Polarized emission from stretched PPV films viewed at the molecular level. Issue 32 (22nd July 2015) - Ramos, Rodrigo; Siqueira, Melissa F.; Cazati, Thiago; Faria, Roberto M.; Caldas, Marilia J.
Abstract : We present a study on the photoluminescence (PL) of thin films of poly-( p -phenylene vinylene) (PPV), non-stretched and uniaxially stretched. Abstract : We present a study on the photoluminescence (PL) of thin films of poly-( p -phenylene vinylene) (PPV), non-stretched and uniaxially stretched. The experimental study was carried out using linear polarized light as the excitation beam, oriented either parallel or perpendicular to the stretch axis ( S ). The results showed that when the excitation light source has polarization perpendicularly oriented to the stretch direction, the emitted PL presents maximum intensity in the orientation S, and a minimum in the direction orthogonal to S . In order to understand this interesting phenomenon, we employ theoretical simulations at the atomistic level. We use classical molecular dynamics to simulate amorphous PPV films, non-stretched and stretched, from which we find a tendency of overall alignment of PV units to S, and of local clustering in herring-bone and π-stacking partial symmetries. Our study of optical activity of these kinds of clusters, performed through a quantum semi-empirical method, allows us to explain this polarization conversion behavior, and indicates the possibility of using underivatized PPV as the active layer for polarized electroluminescent devices.